Getting at Gendered Inequalities in Food Security in Covid-19 - van de Velde, Patricia (2021)
Patricia van de Velde POLICY SEMINAR Towards Resilient Livelihoods, Food Security, and Nutrition for All: Confronting the Gendered Impacts of COVID-19 Co-Organized by IFPRI, the United States Agency for International Development (USAID) and the World Bank MAR 23, 2021 - 09:30 AM TO 11:00 AM EDT